Chiral fermions on the lattice - Jahn, Oliver; Pawlowski, Jan M. (Arxiv, 2002)
We discuss topological obstructions to putting chiral fermions on an even dimensional lattice. The setting includes Ginsparg-Wilson fermions, but is more general. We prove a theorem which relates the total chirality to the difference of generalised winding numbers of chiral projection operators. For an odd number of Weyl fermions this implies that particles and anti-particles live in topologically different spaces.
Gesehen am 06.12.2017